Rapid and non‐invasive evaluation of pork meat quality during storage via impedance measurement. (21st May 2015) - Nguyen, Han B.; Nguyen, Loc T.
Summary In this study, the evolutions of impedance and bio‐indicators (total aerobic count (TAC), total volatile base nitrogen (TVB‐N) and pH) of meat freshness during storage at 4 °C were investigated and compared. The influence of electrode configurations, frequencies and directions of applied electric fields on impedance measurement was considered. Good relationships between measured impedance and bio‐indicators were obtained, with R2 ranging from 0.758 to 0.992, RMSE from 0.11 to 0.57 for TAC and R2 ranging from 0.636 to 0.989, RMSE from 0.29 to 1.68 for TVB‐N. Bar and ring electrodes had better performance as compared to needle electrodes. Effects of frequency on impedance were important from 20 Hz to 200 kHz and diminished in the higher ranges. Impedance generally exhibited better correlations with TAC, TVB‐N at high frequency than at low frequency. The findings demonstrated that impedance measurement could be a viable, rapid method to assess the quality of stored pork meat.